New Asia forum - Rodhiah Abu Yazid (Petaling Jaya : Sistem Televisyen Malaysia Berhad, 1996)
Forum was held in January 1996, disscused Asia in the new millenium. How the Asian countries reshaping Asia to the new millenium. The theme for this forum is'How Asian Enterprise is transforming the global economy'
Copy available in DVD format
Narrator, Rodhiah Abu Yazid
Keywords: Asia -- Politics and government; Asia -- Social conditions; Asia -- Economic conditions